Clinicopathological and molecular profiling of sporadic synchronous multiple primary colorectal cancers: focus on microsatellite instability status - Lv, Kai; Yang, Hui; Xi, Xiangpeng; Liu, Yulin; Zhang, Yongbo; Chen, Jingbo (Journal of Gastrointestinal Oncology, 2026)
Background: Sporadic synchronous multiple primary colorectal cancer (SSCRC) is uncommon, and its molecular features remain unclear. This study aimed to compare the clinicopathological and molecular characteristics of SSCRC with solitary colorectal cancer and to evaluate microsatellite instability (MSI) status across synchronous lesions.Methods: We retrospectively enrolled 46 patients with synchronous CRCs and 202 patients with solitary CRCs. MSI status was determined for each SSCRC lesion using polymerase chain reaction (PCR)-based testing. Additional clinicopathological variables and selected molecular features were also assessed.Results: Compared with solitary CRC, SSCRC index lesions were associated with more advanced clinicopathological features (all P